2005
DOI: 10.1007/s00068-005-1405-5
|View full text |Cite
|
Sign up to set email alerts
|

Open Wedge Osteotomy for Malunited Extraarticular Distal Radius Fractures with Plate Osteosynthesis without Bone Grafting

Abstract: Ab stractBackground: Malunion of distal radius fractures can cause pain, limited wrist motion, or loss of grip strength. The most important factors are incongruity in the distal radioulnar (DRU) joint and radial tilt which causes adaptive carpal instability. The purpose of open wedge corrective osteotomy is to restore congruency with minimal soft-tissue damage. Patients and Methods: Between 1993 and 2001, 47 patients with malunited extraarticular distal radius fractures who were treated by open wedge correctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…The study showed improvement in functional and radiographic outcomes regardless of type of plate fixation and fracture type. 40 These results are also consistent with those of a prospective study in which 22 malunions with dorsal angulation were treated with open wedge osteotomy and volar locked plates without bone grafts. 41 Another study retrospectively evaluated 28 patients with an extra-articular malunion of the distal radius.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The study showed improvement in functional and radiographic outcomes regardless of type of plate fixation and fracture type. 40 These results are also consistent with those of a prospective study in which 22 malunions with dorsal angulation were treated with open wedge osteotomy and volar locked plates without bone grafts. 41 Another study retrospectively evaluated 28 patients with an extra-articular malunion of the distal radius.…”
Section: Discussionsupporting
confidence: 89%
“…All studies reported no problems with bone healing. [40][41][42][43] The study of Wieland et al was the first published study that retrospectively evaluated 47 extra-articular malunions treated without the use of bone grafts. The study showed improvement in functional and radiographic outcomes regardless of type of plate fixation and fracture type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The excellent healing potential of the metaphyseal region of the distal radius ( Prommersberger et al 2002a ) has made the need for a bone graft questionable, and in a series of 35 cases ( Wieland et al 2005 ) and more recently in a series of 22 cases ( Mahmoud et al 2012 ), no non-unions were reported, despite the fact that no bone graft was used.…”
mentioning
confidence: 99%